DNA sequence of the lactose operon: the lacA gene and the transcriptional termination region. - Hediger, M A (1985)
The lac operon of Escherichia coli spans approximately 5300 base pairs and includes the lacZ, lacY, and lacA genes in addition to the operator, promoter, and transcription termination regions. We report here the sequence of the lacA gene and the region distal to it, confirming the sequence of thiogalactoside transacetylase and completing the sequence of the lac operon. The lacA gene is characterized by use of rare codons, suggesting an origin from a plasmid, transposon, or virus gene. UUG is the translation initiation codon. A preliminary examination of 3' end of the lac messenger in the region distal to the lacA gene indicates several endpoints. A predominant one is located at the 3' end of a G + C-rich hairpin structure, which may be involved in termination of transcription or in post-transcriptional processing. An open reading frame of 702 base pairs is present on the complementary strand downstream from lacA.